STRATEGI KOMUNIKASI KEBIJAKAN DINAS PEMADAM KEBAKARAN DALAM PENCEGAHAN DAN PENANGGULANGAN KEBAKARAN DI PERMUKIMAN PADAT KECAMATAN KEBON JERUK JAKARTA BARAT - Alfin Firmansyah; Masniah Ahmad; Hendra Wijayanto (Program Studi Ilmu Pemerintahan, 2024)
Urban or residential fires generally occur in city areas that have dense settlements, because the conditions of the buildings are not well organized. Apart from that, the condition of settlements in several areas of West Jakarta, especially Kebon Jeruk District, has a high building density. For the type of building material characteristics, residents' houses are divided into two groups, namely the type of permanent house, namely houses that have fire-resistant materials (wall type of house). And semipermanent houses, namely houses that use a lot of wood material, which for this type of house is a house that is vulnerable to fire. As well as a lack of awareness and care from residents because household equipment that has reached the end of its useful life is still being used, this condition is the background to how the strategy is implemented fire prevention communication by the Fire Department in preventing and dealing with fire disasters by providing outreach, appeals, forming volunteer fire fighters, pasting fire prevention stickers and building independent hydrants for residents. The aim of this research is to determine the communication strategy of the Kebon Jeruk District Fire Department in Preventing and Managing Fire Disasters in Dense Settlements. This research uses a descriptive qualitative method with a case study approach that focuses on one institution. This research data collection used interview methods, observation, and data collection with documents. The results of this research show that implementing a communication strategy from the fire department can minimize the number of fires in densely populated areas, but there are still several areas that are still fire-prone areas in densely populated areas, Kebon Jeruk District, West Jakarta. This is still homework for the fire service.